Shifting Teachers' Attitudes or Developing Innovative Didactical Designs: Which Should Come First? - Anton Nasrullah; Didi Suryadi; Agus Hendriyanto; Lukman Hakim Muhaimin (STAI Hubbulwathan Duri, 2025)
In mathematics education, the process of knowledge transposition—how academic content is adapted for classroom use—is shaped by teachers’ attitudes and instructional practices. In Indonesia, little is known about how mathematics teachers critically engage with textbooks and curricular materials during this process. This qualitative study employed an interpretative phenomenological analysis to explore the lived experiences of five experienced mathematics teachers from reputable schools in Bandung and Surakarta. Data were collected through semi-structured, in-depth interviews and analyzed thematically to uncover patterns in teachers’ perceptions and practices related to instructional materials. The findings reveal a strong reliance on textbooks as primary teaching references, often accompanied by uncritical acceptance of their content. Teachers tended to assume that government-issued or commercially published textbooks were scientifically accurate, without cross-referencing them against academic sources. This passive approach to knowledge adaptation raises the risk of perpetuating conceptual misunderstandings in the classroom. While some teachers expressed skepticism, they lacked the confidence or institutional support to challenge existing materials. These results suggest a need for professional development programs that promote critical curriculum analysis, reflective teaching practices, and collaborative content evaluation. Supporting teachers to act not merely as content deliverers, but as informed and critical mediators of knowledge, is essential for effective didactic transposition and improved student learning outcomes.